UPAYA PENINGKATAN MENULIS KARANGAN NARASI PADA PEMBELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN METODE BRAINSTORMING DI KELAS IV SD MAARIF NU 01 SONGGOM BREBES - Sela Mukholifati; Abdul Halim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of narrative writing skills among fourth-grade students is caused by monotonous teaching methods. This study aims to examine improvements in these skills through brainstorming. The research subjects were 20 students at Maarif NU 01 Elementary School in Songgom, Brebes. The classroom action research, based on the Kemmis and McTaggart model, spanned two cycles. Data were collected through tests and observations. The instruments included tests, teacher-student observation sheets, and validation by subject matter and language experts. In Cycle I, the average score for students’ narrative writing skills was 63.4, with a mastery rate of 45% of students achieving “Mastery”; this improved in Cycle II, with an average score of 71.75 and a mastery rate of 75% of students achieving “Mastery.” In addition, improvement was also evident in the results of observations of student activities. The average score from student observations in Cycle I was 68, with a mastery rate of 50%; this improved in Cycle II to an average score of 75.25, with a mastery rate of 80%. Based on these test and observation results, the conclusion of this study is that the use of the brainstorming method can improve narrative writing skills among fourth-grade students at SD Maarif NU 01 Songgom Brebes. This brainstorming method also received positive feedback from both teachers and students.